Tirzepatide: a turning point in obesity related heart failure with preserved ejection fraction? - Rahemeen Goraya; Anfal Babar Saeed (Journal of the Pakistan Medical Association, 2026)
Madam, Heart failure with preserved ejection fraction (HFpEF) is a prevailing health concern across the world. It is commonly defined as heart failure with an ejection fraction of 50% or above.1 It presents as a major complication in people with diabetes and obesity(diabesity).2 Over the years, obesity has been a major culprit in the development and progression of various complications like diabetes, chronic kidney disease, atherosclerotic cardiovascular disease, coronary artery calcification, and heart failure.2 Comprehensive research is required to explore its role in disease progression and to determine the interplay of diabetes, obesity, and heart failure (HF) Unlike Heart failure with reduced ejection fraction (HFrEF), there has been little research on the treatment and management of HFpEF. Current treatment regimen for HFpEF includes drugs such as SGLT2 inhibitors, diuretics, renin–angiotensin–aldosterone system (RAAS) inhibitors, and beta blockers. However, none of these directly targets obesity. Tirzepatide, a glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide 1 (GLP-1)receptor agonist, has been widely used in the treatment of diabetes mellitus due to its significant weight-reducing effects along with regulation of blood glucose levels. Recent studies demonstrate the multiorgan therapeutic effect of tirzepatide due to the presence of GLP1 receptors in other organs such as the brain, heart, pancreas, stomach, and endometrium.3 Its benefits in cardiovascular outcomes are an area of active investigation.. Ongoing clinical trials have showed that tirzepatide significantly reduces heart failure events and mortality in obesity induced HFpEF by various mechanisms; reduction of Left Ventricular mass, pericardiac adipose tissue, cardiac compression, obesity-induced inflammation, concentric cardiac remodelling, and improving heart chambers’ compliance and filling. This improves functional capacity, health-related quality of life, exercise tolerance, and reduces the need for multiple heart failure medications.4 This offers a promising future for the control of obesity induced HFpEF in diabetic, non-diabetic, and chronic kidney disease (CKD) patients. The US Food and Drug Administration (FDA) has approved this drug for the treatment of diabetes, and chronic weight management,recently also for obstructive sleep apnea.5 Further clinical trials substantiating the efficacy of tirzepatide in reducing heart failure events may lead to its approval for use in HFpEF treatment. Additionally, long-term safety data arelimited, and further research is crucial to determine its long-term effects.. Clinicians and researchers worldwide should stay informed regarding the potential of this drug and outcomes of the ongoing trials.